(untitled) (Journal of Advanced Research in Social Sciences, 2023)
This study focuses on an exploration of the concept of beauty using the semantic differential method. 2,080 participants (53.46% were female) aged 18 to 89 (M = 41.36 years; SD = 16.48) were asked to evaluate the concept of beauty using twenty-one bipolar adjectives across three semantic differential dimensions – activity, evaluation, and potency. The results indicate that the most descriptive adjectives used to describe beauty are: pleasant, inviting, good, inspiring, pure, and kind, indicating that the concept of beauty is mostly associated with positive connotations. Furthermore, the majority of the characteristic adjectives are related to the evaluation dimension, in which statistically significant differences were identified in the evaluations made by men and women. Women perceive beauty as a concept that is significantly more strongly associated with evaluative judgments than men (p <.01). The potential of the semantic differential method can be used to compare the meaning of the concept of beauty with synonymous and oppositional concepts.